An Efficient Somatic Embryogenesis and Plant Regeneration from Immature Embryo of Wild Banana Musa acuminata ssp. malaccensis - Handayani, Tri; Martanti, Diyah; Prawestri, Apriliana Dyah; Maharijaya, Awang; Wahyu, Yudiwanti; Sobir; Witjaksono (Department of Agronomy and Horticulture, IPB University, 2025)
Wild banana Musa acuminata ssp. malaccensis, an ancestor of cultivated bananas, possesses valuable genetic diversity, including resistance genes to fusarium wilt, and demonstrates high environmental adaptability. These traits are important for pre-breeding programs, whether by conventional breeding, which is a lengthy process, or by taking advantage of somatic cell manipulation techniques such as somatic hybridization, which requires an efficient plant regeneration system like somatic embryogenesis. We have established an efficient and comprehensive protocol for somatic embryogenesis of this wild Musa using immature zygotic embryo explants covering culture induction and proliferation, somatic embryo development, and subsequent plant conversion. Embryogenic culture was induced on a complex-modified MS medium supplemented with 1 mg.L-1 2,4-D auxin or 5 mg.L-1 picloram. The embryogenic cultures proliferated in the form of granular or nodular structures, which was best obtained by reducing the picloram concentration to 1 mg.L-1 and combining it with the same concentration of 2,4-D at a half-strength macro-nutrient of basal medium. Embryo development from embryogenic cultures and regeneration into shoots. Proembryos as granular structures spontaneously matured into early-stage somatic embryos upon withdrawal of the strong auxin inducer. Increasing the sucrose and gelling agent concentrations in the growth medium improved somatic embryo formation from embryogenic cultures. The frequency of shoot formation from developed somatic embryos was increased by incorporating 0.5 mg.L-1 BA and 0.5 mg.L-1 GA3 into the regeneration medium.